Mental health in times of crisis: increase in the occurrence of mental suffering, policy erosion, and conservative reversal - Garcia, Maria Lúcia T.; Leal, Fabíola Xavier (Argumentum, 2023)
Editorial do V. 15, n. 3, set./dez. 2023.